Religiousness and the Question of Existence of Erich Fromm - AlaAlddin, Ghassan; Abboud, Janet (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
Existence imposes itself, as viewed by Erich Fromm, on Man who finds himself lost in it, anxious about it and busy with the way he deals with the world. An existence that keeps changing until it almost gets hard to seize it intellectually in order to know it and the suitable techniques to deal with it and utilize it for the sake of Man to give value and meaning to his life. However, it is not possible for Man to do so unless he skillfully asks the question related to existence in a right way, which extremely helps in providing reasonable answers about all matters that occupy Man, which concern the purpose of his existence in this world, his place in it and the role he is supposed to take so that he fully achieves his humanity. This is only possible when Man resorts to existence, lives it, and cooperates with the other who shares living in it, likes him, and also seeks to offer answers about what concerns him regarding his relation with religion, which Man always finds himself forced to accept as it offers him safety and satisfaction. يفرض الوجود - كما يرى إريك فروم - على الإنسان الذي يجد نفسه تائهاً فيه، قلقاً منه، مشغولاً بالطريقة التي يتعامل بها مع عالم أو وجود لا ينفك يتبدل ويتغير حتى يكاد يصعب القبض عليه فكرياً بغية معرفته وبالتالي الوقوف على الأساليب المناسبة للتعاطي معه وتجييره لصالح الإنسان لإضفاء قيمة ومعنى على حياته. بيد أنه لن يتسنى للإنسان أن يفعل ذلك مالم يجيد طرح السؤال الذي يتعلق بالوجود على نحو صحيح يسهم إلى حد بعيد في تقديم إجابات معقولة حول كل ما يشغل الإنسان من مسائل تتعلق بجدوى وجوده في هذا العالم أصلاً، ومكانته فيه، والدور الذي يفترض أن يضطلع فيه كي يحقق إنسانيته على أكمل وجه، وهذا لن يكون من غير أن يرتمي الإنسان في أحضان الوجود ويعيشه، ويتعاون مع الآخر الذي يقاسمه العيش فيه ويحبه، ويسعى بالتالي لتقديم إجاباته عما يشغل باله في إطار علاقته بالدين، الذي سيجد المرء نفسه دائماً مضطراً لقبوله لما يمنحه له من طمأنينة ورضى وسلام.